Ministry of Trade and Industry Decree No. 195 of the Year 2022 On Amending the Rules Organizing the Registration of the Factories Qualified to Export the Products Thereof to the Arab Republic of Egypt = وزارة التجارة والصناعة قرار رقم 195 لسنة 2022 بشأن تعديل القواعد المنظمة لتسجيل المصانع المؤهلة لتصدير منتجاتها إلى جمهورية مصر العربية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic